Multiple Myeloma Cells Express Key Immunoregulatory Cytokines and Modulate the Monocyte Migratory Response - Freire-de-Lima, Leonardo; Nardy, Ana Flávia Fernandes Ribas; Ramos-Junior, Erivan Schnaider; Conde, Luciana; Santos Lemos, Jéssica; Fonseca, Leonardo Marques da; Lima, Juliana Echevarria; Maiolino, Angelo; Morrot, Alexandre (Frontiers in Medicine, 2017)
Multiple myeloma (MM) is a plasma cell disorder that still remains incurable. The immune dysfunction of the host is a striking characteristic of MM, leading to tumor growth and reducing the survival rate of patients. Monocytes are precursors of conventional dendritic cells (DCs), a major player in the immunity mechanisms driving protective T cell responses against tumor. Herein, we report that human MM RPMI 8226 cell line shows a pronounced chemoattractant activity for monocytes and also expresses enhanced levels of the leukocyte chemotactic cytokines CXCL12, CCL5, MIP-1β, and CXCL10 in association with elevated levels of both key immunoregulatory interleukins such as IL-4 and IL-10. This cytokine profile was observed together with reduced expression of IFN-γ by MM RPMI 8226 cell line, a determinant interleukin involved in the acquisition of cellular-mediated protective responses against tumor cells. We further demonstrate that MM RPMI 8226 cell line expresses elevated levels of soluble form of the intercellular adhesion molecule-1 known to inhibit antitumoral T cell responses. This attractive modulation of immune responses by MM cells might provide a means to impair early antitumor responses during the establishment of cytokine-mediated immunosuppressive tumor niche.